Preoperative patients' quality of life and outcomes after colorectal surgery: A prospective study. Issue 44 (5th November 2021) - Martin, David; Romain, Benoît; Demartines, Nicolas; Hübner, Martin
Abstract : Abstract: The aim of this prospective study was to assess the influence of preoperative life satisfaction on objective and subjective outcomes after elective colorectal surgery. Preoperative life satisfaction was assessed using a validated questionnaire (Échelle de Mesure des Manifestations du Bien-Être Psychologique). Postoperative quality of life was assessed by the Cleveland Global Quality of Life and QLQ-C30. Number of footsteps was recorded from preoperative day 5 to postoperative day 3. Physical activity, length of stay, and complications were compared between patients with low and high preoperative life satisfaction. Fifty patients were included. There was no difference between the 2 groups concerning postoperative objective (length of stay, complications, and number of footsteps) and subjective (Cleveland Global Quality of Life and QLQ-C30) recovery. In conclusion, preoperative life satisfaction of colorectal surgery patients had no influence on outcomes and physical activity in colorectal surgery.